2014
DOI: 10.1371/journal.pone.0097586
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Partial Volume Effects in Arterial and Venous Contrast Curves in CT Brain Perfusion Imaging

Abstract: PurposeIn brain CT perfusion (CTP), the arterial contrast bolus is scaled to have the same area under the curve (AUC) as the venous outflow to correct for partial volume effects (PVE). This scaling is based on the assumption that large veins are unaffected by PVE. Measurement of the internal carotid artery (ICA), usually unaffected by PVE due to its large diameter, may avoid the need for partial volume correction. The aims of this work are to examine i) the assumptions behind PVE correction and ii) the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…Riordan et al. showed that ICA in patients with normal cerebral circulation is unaffected by PVE [15]; however, in our study mean contrast enhancement in ICA was relatively low −346 HU; therefore, PVE could not be corrected sufficiently. This might result in overestimation of perfusion parameters.…”
Section: Discussioncontrasting
confidence: 82%
“…Riordan et al. showed that ICA in patients with normal cerebral circulation is unaffected by PVE [15]; however, in our study mean contrast enhancement in ICA was relatively low −346 HU; therefore, PVE could not be corrected sufficiently. This might result in overestimation of perfusion parameters.…”
Section: Discussioncontrasting
confidence: 82%
“…In brain imaging, arteries typically are small, making VF selection challenging with respect to avoiding signal contributions from the surrounding non‐vascular tissue. This problem, known as the partial volume effect (PVE), can result in the area under the VF curve being underestimated, possibly compromising the estimation of hemodynamic parameters 9–11 . Cerebral venous structures have the advantage of tending to be larger thus reducing the impact of PVE.…”
Section: Introductionmentioning
confidence: 99%
“…This problem, known as the partial volume effect (PVE), can result in the area under the VF curve being underestimated, possibly compromising the estimation of hemodynamic parameters. [9][10][11] Cerebral venous structures have the advantage of tending to be larger thus reducing the impact of PVE. In addition, because the blood flow velocity is higher in arteries than in veins, the observed arterial signal intensity can decrease due to signal dephasing.…”
Section: Introductionmentioning
confidence: 99%